ANALYSIS OF THE EFFECTIVENESS OF NATURAL INGREDIENTS IN ANTHYPERURICEMIA:REVIEW - Angela, Elva; Susanti; Diniatik (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Introduction: Hyperuricemia is characterized by increased uric acid levels in the blood due to excessive production or impaired excretion. In Indonesia, the hyperuricemia rate reaches 18% of the total population. Objective: This study aimed to explore and analyze the potential of medicinal plants with antihyperuricemic activity in reducing uric acid levels in patients with hyperuricemia and experimental animals. Materials and Methods A total of 21 scientific articles were reviewed, focusing on the treatment of hyperuricemia using natural ingredients. Data were obtained from the Google Scholar and PubMed databases using keywords such as “hyperuricemia,” “medicinal plants,” and “natural therapy.” The inclusion criteria were articles published within the last 10 years that involved in vitro and in vivo models.  Results: The review identified several natural ingredients, including turmeric, kepel leaves, and mangosteen peel, which demonstrated significant antihyperuricemic effects. These ingredients were effective in reducing uric acid levels in both animal and human studies.Conclusion: Natural ingredients show promising potential as alternative treatments for hyperuricemia by inhibiting xanthine oxidase activity. However, further clinical trials are required to validate these findings and support their application in therapeutic practice. Keywords: Antihyperuricemia, Uric Acid, Natural Ingredients, Clinical Trials